Using Podcasts As English Learning Media to Improve Student Listening Skills - Mellina; Suswanto Ismadi Megah Saputro; Sri Sugiharti (South Sulawesi Education Development (SSED), 2025)
This study investigates the urgency of finding innovative and effective methods to improve students' listening skills in English, a critical component of language learning often hindered by a lack of engaging resources. The research aimed to evaluate the effectiveness of audio podcasts in addressing this challenge and enhancing students' listening comprehension. A quasi-experimental design was employed, involving 25 students who participated in a pretest-posttest framework. The intervention included regular exposure to audio podcasts specifically designed to improve listening skills. Data were collected through pretest and posttest scores, along with an analysis of student feedback. The results revealed a significant improvement in students' listening abilities, with the average posttest score increasing from 51.76 to 63.63. Furthermore, 13 out of 25 students achieved the KKM score, a substantial increase from only one student in the pretest. This study underscores the potential of audio podcasts as an engaging and accessible tool for language learning. By demonstrating their effectiveness in enhancing listening comprehension and student engagement, the research highlights the practicality of incorporating podcasts into language teaching as an alternative to traditional methods. These findings emphasize the urgency of integrating innovative tools like podcasts to make listening practice both enjoyable and impactful in modern language education.